Production Performances of Joper Chicken Fed Fermented Azolla pinnata - Muhamad Suryadinata; I Ketut Gede Wiryawan; Vebera Maslami (Jurnal Biologi Tropis, 2026)
The instability of animal feed prices has encouraged the utilization of alternative feed ingredients to partially replace commercial rations. This study aimed to evaluate the effect of fermented Azolla pinnata inclusion at different levels on feed intake, body weight gain, feed conversion ratio (FCR), crude protein intake, and crude fiber intake of Joper chickens. The research was conducted under a completely randomized design that included five dietary treatments: P0 (100% commercial feed), P1 (15% unfermented Azolla pinnata), P2 (10% fermented Azolla pinnata), P3 (15% fermented Azolla pinnata), and P4 (20% fermented Azolla pinnata). The results showed that feed intake and FCR were not significantly affected by dietary treatments. However, body weight gain, crude protein intake and crude fiber intake differed significantly among treatments. The lowest crude protein intake was observed in chickens fed unfermented Azolla pinnata (P1), while diets containing fermented Azolla pinnata maintained crude protein intake comparable to the control diet. Crude fiber intake increased with higher levels of Azolla pinnata inclusion, particularly in the non-fermented treatment. In conclusion, the inclusion of Azolla pinnata, either unfermented or fermented, did not affect feed intake and FCR of Joper chickens, but significantly influenced body weight gain, crude protein and crude fiber intake. The inclusion of 10% fermented Azolla pinnata provided the most optimal result by maintaining body weigt gain and higher protein intake with a relatively more stable crude fiber approaching the control, thus supporting efficient nutrient utilization and production performance of joper chickens.